ЛОҚАЙДЛИК ВА БЕПАРВОЛИК ЁШЛАР ТАРБИЯСИДА ИЛЛАТ СИФАТИДА - Шерманов, Э. (SCIENCE and SOCIETY, 2022)
In the article, issues of developing the virtue of involvement in reforms in the formation of the worldview of the young generation, shortcomings in youth education, impoverishment of spirituality, issues of attention to education of involvement in the process of civil society formation.